TRAINING TOUR GUIDES AND TRANSLATORS USING AUTHENTIC VIDEO MATERIALS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the methodology of training tour guides and translators through the use of authentic video materials. The relevance of this study is underscored by the growing demands for quality services in the tourism industry and the necessity for enhancing the professional skills of translators in the context of globalization. The article analyzes the advantages of using video as an educational resource, describes various types of authentic materials, and their impact on the development of linguistic and cultural competencies among students. Furthermore, it discusses successful practices of integrating video into the educational process and provides recommendations for creating effective training programs. In conclusion, the article summarizes the findings and outlines prospects for further research in this area.